Corresponding assessment scenarios in laboratory and on-court tests: Centrality measurements by complex networks analysis in young basketball players - Gobatto, C. A.; Torres, R. S.; Moura, F. A.; Cunha, S. A.; Giometti, C. B.; Araujo, G. G.; Sousa, F. A. B.; Manchado-Gobatto, F. B. (Scientific Reports, 2020)
Besides technical and tactical aspects, basketball matches involve high aerobic and anaerobic capacities, conferring the final performance of a team. Thus, the evaluation of physical and technical responses is an effective way to predict the performance of athletes. Field and laboratory tests have been used in sports. The first involving high ecological validity and low cost, and the second, greater control and accuracy but not easy application, considering the different preparation phases in a season. This study aimed, through complex networks analysis, to verify whether centrality parameters analysed from significant correlations behave similarly in distinct scenarios (laboratory and on-court), emphasizing aerobic and anaerobic physical parameters and technical performances. The results showed that, in a compelling analysis involving basketball athletes, the studied centralities (degree, betweenness, eigenvector and pagerank) revealed similar responses in both scenarios, which is widely attractive considering the greater financial economy and lower time when applying tests in the field.